Micronutrient status 2 years after bariatric surgery: a prospective nutritional assessment - Côté, Marianne; Pelletier, Laurence; Nadeau, Mélanie; Bouvet-Bouchard, Léonie; Julien, François; Michaud, Andréanne; Biertho, Laurent; Tchernof, André (Frontiers in Nutrition, 2024)
Background: Among commonly performed bariatric surgeries, biliopancreatic diversion with duodenal switch (BPD-DS) provides greater weight loss than Roux-en-Y gastric bypass (RYGB) or sleeve gastrectomy (SG), with sustained metabolic improvements. However, the risk of longterm nutritional deficiencies due to the hypoabsorptive component of BPD-DS hinders its widespread use.The aim of the study was to examine nutritional status over 2 years after BPD-DS, RYGB or SG.: Patients were recruited in the REMISSION trial (NCT02390973), a single-center, prospective study. Out of 215 patients, 73, 48 and 94 respectively underwent BPD-DS, RYGB or SG. Weight loss, micronutrient serum levels (including iron, calcium, parathormone, vitamins A, B12 and D), and nutritional supplementation were assessed over 2 years. Patients were supplemented according to the type of surgery and individual micronutrient level evolution.Results: At baseline, BPD-DS patients were younger than SG patients (p=0.0051) and RYGB patients had lower body mass index (p<0.001). Groups had similar micronutrient levels before surgery, with vitamin D insufficiency as the most prevalent nutritional problem (SG: 38.3%, RYGB: 39.9%, BPD-DS: 54.8%, p=0.08). BPD-DS patients showed lower levels of iron, calcium and vitamin A than SG patients at 24 months. Groups had similar levels of vitamin D at 24 months.Prevalence of vitamin D, calcium, iron, vitamin A and vitamin B12 deficiency was similar among groups at 24 months. Rates of vitamin D insufficiency and iron deficiency were lower at 24 months than at baseline. Micronutrient intake was consistent with recommendations in groups postsurgery, but most BPD-DS patients took vitamin A and vitamin D supplement doses above initial recommendations.With appropriate medical and nutritional management, all surgeries led to similar rates of vitamin D, calcium, iron, vitamin A and vitamin B12 deficiencies at 24 months. However, initial vitamin A and vitamin D supplementation recommendations for BPD-DS patients should be revised upwards.